Maintenance for air conditioning / Hazim Ahmad Danial Ahmad Hashimi - Ahmad Hashimi, Hazim Ahmad Danial (Universiti Teknologi MARA, Perak, 2022)
Air conditioning (often referred to as AC, or air con) is a system used to cool down the temperature in an inside space by removing the existing heat and moisture from the room. Thus, it is also important to do the maintenance process for the air conditioning to keeps the air conditioning in the building runs as good as new. It is also to keep the temperature inside the building to always cool and comfortable for the people inside the building. This report will discuss about maintenance service of air conditioning. This report was conducted for University of Reading Malaysia, which is located at Kota Ilmu, Persiaran Graduan, Educity, Nusajaya, Johor Darul Takzim. The objective of the report is to analyze the maintenance process of air conditioning and how it carried out. It will focus on the whole process of maintenance service for central air conditioning, split air conditioner and cassette air conditioner.